PERKEMBANGAN PENELITIAN MENGENAI PERGANTIAN AUDITOR - Mustofa, Abdurrahman Zaki (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2019)
This study aims to provide an overview of the development of the research related to audit switch, the samples taken from various national journal that can be accessed online. 18 samples taken from 9 national journals with the time span of 2009 to 2018. This research use Charting the Field method that was developed by Hesford et al (2007) where the researcher classified articles based on the topic and research method that is used on the articles. The results show that the most researched variable is Pergantian Manajemen. Research topic related to audit switch that is researched the most is anteseden topic, using Pergantian Manajemen Variable. The research method that is used the most is analytic method and among all samples there is no article that use review method.